2017
DOI: 10.1021/acsphotonics.7b01486
|View full text |Cite
|
Sign up to set email alerts
|

High Responsivity β-Ga2O3 Metal–Semiconductor–Metal Solar-Blind Photodetectors with Ultraviolet Transparent Graphene Electrodes

Abstract: We demonstrated high responsivity metal–semiconductor–metal (MSM) solar-blind photodetectors by integrating exfoliated β-Ga2O3 microlayers with graphene, which is a deep ultraviolet (UV) transparent and conductive electrode. Photodetectors with MSM structures commonly suffer from low responsivity, although they feature a facile fabrication process, low dark current, and fast response speed. The β-Ga2O3 MSM solar-blind photodetectors with graphene electrodes exhibited excellent operating characteristics includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
142
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(152 citation statements)
references
References 33 publications
9
142
1
Order By: Relevance
“…According to the above equations, the NEP was calculated to be ≈1.73 × 10 −16 W Hz −1/2 , which led to a D * value of ≈8.16 × 10 12 Jones. Such a high D * value is comparable with the values of a single‐crystalline Sn‐doped β‐Ga 2 O 3 wafer/graphene heterojunction DUV photodetector (≈10 13 Jones) and a exfoliated single‐crystalline β‐Ga 2 O 3 microflake MSM DUV photodetector with graphene electrodes (≈1.45 × 10 12 Jones) …”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…According to the above equations, the NEP was calculated to be ≈1.73 × 10 −16 W Hz −1/2 , which led to a D * value of ≈8.16 × 10 12 Jones. Such a high D * value is comparable with the values of a single‐crystalline Sn‐doped β‐Ga 2 O 3 wafer/graphene heterojunction DUV photodetector (≈10 13 Jones) and a exfoliated single‐crystalline β‐Ga 2 O 3 microflake MSM DUV photodetector with graphene electrodes (≈1.45 × 10 12 Jones) …”
Section: Resultssupporting
confidence: 56%
“…To date, a number of DUV photodetectors based on β‐Ga 2 O 3 in the form of either thin films or nanostructures have been successfully developed . Benefiting from quantum confinement effect and remarkable surface/size effect, β‐Ga 2 O 3 nanostructures, in particular 1D β‐Ga 2 O 3 nanowires (NWs) or nanobelts (NBs), can exhibit attractive merits of better optical absorption, improved charge carrier transportation, and increased surface states to interact with surroundings, over their thin films' counterpart .…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the photocurrent was varied lesser than the dark current with temperature increment. Photocurrent to dark current (PDCR) ratio is also an essential parameter of photodetectors which was calculated using the following equation: [36][37]…”
mentioning
confidence: 99%
“…Excellent solar-blind performance with high responsivity and low dark currents have been reported for β-Ga 2 O 3 deep-UV photodetectors. 6,[26][27][28][29][30][31][32] Both Schottky 14,17,27,30,[32][33][34] and metal-semiconductor-metal (MSM) 7,9,13,[19][20][21]35,36) type device architecture have been studied on bulk as well as epitaxial β-Ga 2 O 3 on foreign substrates. Battery-free, self-powered UV detectors reduce the weight and power supply requirement of imagers and prove to be beneficial in terms of reducing the footprint and complexity of systems.…”
mentioning
confidence: 99%
“…(4), the averaged value of D + considering the contributions from thermal noise and noise due to dark current was estimated to be 2.0 × 10 12 Jones at 1 V which matches with the reported values. 7,15,35) Such high detectivity value of photodetectors is suitable to enable planar focal plane arrays using readout integrated circuit (ROIC). vertical Schottky detectors respectively, yet there has been no report on zero-bias responsivity for planar and epitaxial β-Ga 2 O 3 UV photodetectors with MSM based architecture.…”
mentioning
confidence: 99%